Balanced scorecard: Of utility or futility in the financial and production sector - Azher Subhi Abdulhussein, Jasim Idan Barrak, Mushtaq Talib Abdulameer, (Opción, 2019)
This study aims to understand the applicability of balanced scorecard systems in two UAE-based firms, Al Masraf Bank and Alba Gold Manufacturing LLC, relating to its relevance on their performance management. The research follows a positivist philosophy with a focus on quantitative data. As such, the method utilizes a mono-method of quantitative nature for its primary data collection. As a result, the complexity, time consuming and expensive nature of the approach makes it inefficient for Alba Gold Manufacturing. The study concludes that it is pertinent to incorporate balanced scorecard for the Islamic financing firm.